IMPLEMENTASI KUIS INTERAKTIF BERBASIS HOTS BERORIENTASI KEARIFAN LOKAL DAERAH MELALUI APLIKASI QUIZIZZ DI SEKOLAH DASAR - Tyas Deviana; Nawang Sulistyani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The Covid 19 pandemic caused the need for an adaptation in all areas including in the field of education. The online learning was the way to adapt with the pandemic. Many institutions increased their human resources through training for the preparation of online learning tools. The result was that the teachers were able to make HOTS-based interactive quizzes oriented on local wisdom at Kab. Tulungagung through the quizizz application and its implementation. The goal was that interactive quizzes through the quizizz application could be applied and provided benefits to online learning. This study aimed to analyze the implementation of HOTS-based interactive quizzes oriented on local wisdom at Kab. Tulungagung. The scope of this research included question making, interactive quiz implementation, and evaluation. The study involved 25 students at grade V SDN Mojosari 1 consiting of 11 male and 14 female students. The process of making evaluation questions started from making the question lattice then converted into multiple choice questions by paying attention to HOTS based on local wisdom at Kab. Tulungagung. The implementation of the interactive quiz resulted in the effectiveness of the interactive quiz by 88%. The result of evaluation of HOTS interactive quiz implementation based on local wisdom at Kab. Tulungagung found that 1) interactive quizzes through the quizizz application were needed as an online learning assessment instrument; 2) the use of interactive quizzes eased the teachers to provide assessments without having to make manual corrections as well as being able to analyze the questions made; 3) it fostered competition between students.